A Secure Crypto-Biometric System Utilizing GMM Encoder and BCH (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Now that cloud computing has reached maturity, a diverse array of providers and services are available in the cloud. On the other hand, security issues continue to receive a lot of focus. Despite the many benefits of cloud computing, users are hesitant to embrace the technology due to concerns about their security and privacy. While biometric technologies are rapidly becoming an integral part of many secure identification and personal verification solutions, they do pose certain challenges when stored in the cloud owing to privacy regulations and the requirement to have faith in cloud providers when handling biometric data. In this work, we offer a crypto biometric system that can be used with cloud computing to solve these issues. This system ensures that no private biometric data is revealed.